IMPLEMENTASI KONSEP KEBIJAKAN ONE BELT ONE ROAD (OBOR) CHINA DALAM KERANGKA KERJASAMA PEMBANGUNAN INFRASTUKTUR DI INDONESIA - Muhammad Fahrizal (UIR Press, 2019)
This article discusses the One Belt One Road OBOR Initiative launched by Xi Jinping in 2013, focusing on the role of the initiative in realizing Zhongguomeng. The OBOR initiative is a new infrastructure development project that uses the concept of the New Silk Road that covers geopolitical and geo-economic aspects to connect the Eurasian region with China as its center. The author begins the research by interpreting the background that prompted the Chinese government to implement the OBOR Initiative using historical approaches and qualitative studies, then analyzing the extent to which the OBOR policy can be useful for Xi Jinping to achieve the Zhongguomeng target. The Silk Road was later promoted to become China's new slogan in various international forums. In the view of the current Chinese leader, the concept of the New Silk Road is also known as the